SEEDLING SELECTION OF SORGHUM FOR DROUGHT TOLERANCE BASED ON ROOT MORPHOLOGY - PINTO, DEYVISSON RODRIGUES; MENEZES, CICERO BESERRA; CARVALHO, ABNER JOSÉ; PORTUGAL, ARLEY FIGUEIREDO; MAGALHÃES, PAULO CÉSAR; SILVA, KARLA JORGE; SANTOS, CRISLENE VIEIRA; CAMPOS, ALEXON FERNANDES; DE OLIVEIRA, SIMONICA MARIA; ASPIAZÚ, IGNACIO (REVISTA BRASILEIRA DE MILHO E SORGO, 2023)
Selection for drought tolerance is one of the main challenges of sorghum breeding programs, and early phenotyping, in the seedling phase, can increase selection gains for this trait. This work evaluated characteristics related to root morphology as indicators for early selection of tolerant genotypes to water restriction. Twenty-six hybrids were evaluated, of which twenty-three were experimental and three commercial (BRS310, DKB540 and 1G282). The hybrids were grown in tube-shaped containers in a greenhouse with non-stress stressed water. The evaluated characteristics were Root length (RL), root surface area (SA), root diameter (RD), root volume (RV), surface area of very thin roots (from 0-1 mm in diameter) (SA1), as well as the root/shoot dry mass ratio (R/S). Under water restriction, the hybrids with the best performances for most of the evaluated characteristics were BRS310, 1516057, 1719034, 1719026, 1716041, 1G282, 1516059, 1720052, 1716049, 1718036 and 1716045. The characteristics RV, SA, SA1 and R/S showed the greatest contribution in the selection of these hybrids.